Assessment of Appropriateness of an Initial Dosing Regimen of Vancomycin and Development of a New Dosing Nomogram. Issue 2 (6th September 2017) - Yoon, Seonghae; Park, Kyoung Ryun; Lee, SeungHwan; Song, Sang‐Hoon; Park, Wan Beom; Jang, In‐Jin; Yu, Kyung‐Sang
Abstract: Vancomycin is a glycopeptide antibiotic used to treat Gram‐positive infections including methicillin‐resistant Staphylococcus aureus (MRSA). The objectives of this study were to evaluate the appropriateness of the initial dosing regimen of vancomycin, identify factors to be considered in regimen selection and develop a new dosing nomogram. Therapeutic drug monitoring (TDM) data of vancomycin obtained from Seoul National University Hospital from 2011 to 2013 were included in this analysis. The vancomycin trough concentrations at steady‐state were estimated using Abbott's PKS software program and then categorized into three levels: subtherapeutic, therapeutic and toxic. The newly developed nomograms were evaluated by analysing the percentage of patients with target vancomycin trough concentration using the data of 2, 570 patients of the first TDM cases. Therapeutic level was achieved only in approximately one‐fifth of the cases, while 56.0% and 23.8% of the TDMs were considered subtherapeutic and toxic, respectively. As body‐weight and creatinine clearance (CrCL) increased, the proportion of patients with a subtherapeutic level increased. Using the newly developed nomogram increased the proportion of patients who achieved therapeutic levels from 23.1% to 45.0% or 13.8% to 36.2% (target, 10–15 and 15–20 mg/L, respectively). These results suggest that the vancomycin concentrations fail to reach the therapeutic level or exceed the safe upper margin of the therapeutic level depending on age, body‐weight and CrCL. Considering these factors, the new nomograms provide a strategy to achieve target concentrations of vancomycin more rapidly than existing regimens.